Exchange Rate Flexibility and the Integration of the Securities Market in East Asia - Kinkyo, Takuji; Hamori, Shigeyuki (Journal of Reviews on Global Economics, 2014)
This paper discusses the time-varying degree of flexibility in exchange rate regimes and assesses the extent to which securities markets are integrated in East Asia. The dynamic conditional correlation model developed by Engle (2002) is used to analyze the time-varying characteristics of the conditional correlations of exchange rates as well as of bond and equity returns in emerging Asian economies. First, the presented analyses find that the flexibility of Asia’s exchange rate regimes increased substantially after the Asian crisis of 1997-98. Second, we show that Asia’s equity markets are becoming more globally and regionally integrated, whereas the bond markets in the region are still divided by national borders. These results suggest the existence of more scope for policymakers to promote financial integration in Asia, particularly in its bond markets.